2014
DOI: 10.1590/s0100-06832014000300029
|View full text |Cite
|
Sign up to set email alerts
|

Forms of phosphorus in an oxisol under different soil tillage systems and cover plants in rotation with maize

Abstract: SUMMARYPhosphorus fractions play a key role in sustaining the productivity of acidsavanna Oxisols and are influenced by tillage practices. The aim of this study was to quantify different P forms in an Oxisol (Latossolo Vermelho-Amarelo) from the central savanna region of Brazil under management systems with cover crops in maize rotation. Three cover crops (Canavalia brasiliensis, Cajanus cajan (L.), and Raphanus sativus L.) were investigated in maize rotation systems. These cover crops were compared to spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…M. Carvalho et al (CARVALHO et al, 2012;TALBOT et al, 2012), could have caused the higher C/P ratios found for this species at depths of 0-5 cm during the dry season. Higher C/P ratios in the 0-5 cm soil layer compared to the 5-10 cm layer were caused by lower levels of available P at 0-5 cm compared to at 5-10 cm layer, and by much higher concentration of carbon at the soil surface caused by the accumulation of plant residues, principally maize straw (CARVALHO et al, 2014).…”
Section: Resultsmentioning
confidence: 94%
“…M. Carvalho et al (CARVALHO et al, 2012;TALBOT et al, 2012), could have caused the higher C/P ratios found for this species at depths of 0-5 cm during the dry season. Higher C/P ratios in the 0-5 cm soil layer compared to the 5-10 cm layer were caused by lower levels of available P at 0-5 cm compared to at 5-10 cm layer, and by much higher concentration of carbon at the soil surface caused by the accumulation of plant residues, principally maize straw (CARVALHO et al, 2014).…”
Section: Resultsmentioning
confidence: 94%
“…With the progressive increase in world soybean production it became necessary to find alternative cultivation, such as the implementation of a no-tillage system which can increase soil productivity in a sustainable and economical way by promoting improvements in physical, chemical and biological attributes, helping to protect the soil from erosion and irradiation, besides conserving moisture and providing nutrient cycling, which motivates farmers to use green manure in crop succession and rotation systems (Carvalho et al 2014;Simonetti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…O fósforo total (Pt) no solo é constituído por distintas formas em diferentes graus de disponibilidade às plantas, tais como, inorgânica (Pi) e orgânica (Po), esta última, presente em resíduos de plantas, esterco e tecidos microbianos. O fracionamento químico do P representa uma aproximação dos compartimentos biológicos e geoquímicos que regulam a dinâmica do P orgânico e inorgânico no solo (Carvalho et al, 2014). Através das extrações sequenciais primeiro são obtidas as frações mais lábeis.…”
Section: Introductionunclassified